Viabilidade de implantação de um centro universitário de estudos e pesquisas sobre desastres (CEPED): um mapeamento sistemático - Ribeiro, Fernanda Laís (2017)
There is an overall increase in the occurrence of disasters in recent decades, being essential to Union of sectorial policies, guidelines and educational measures, expanding the necessary culture of disaster prevention. Objective: to systematically map studies related to teaching, research and extension in the management of risk and disaster management, involving agents from civil protection and defense. Method: transversal descriptive quantitative research, with systematic mapping in global databases on disasters. Results: met 43,562 studies, these were articles 5,510. After application of the inclusion/exclusion criteria were 840 articles selected for screening, which totaled 122 articles selected for the systematic mapping. Conclusions: Even with the accelerated increase in the number of global disasters, the publications were inexpressive, mainly nationals. Nevertheless, mapped-if evidence showed that although several challenges are present in the management of risk and disaster management, teaching, research and extension can ensure crucial effects mainly on disaster prevention, as well as improvement of the services provided, and are still low-cost measures for Governments, which led the ranking of publications.